2009
DOI: 10.1158/1541-7786.mcr-09-0043
|View full text |Cite|
|
Sign up to set email alerts
|

A Short Hairpin DNA Analogous to miR-125b Inhibits C-Raf Expression, Proliferation, and Survival of Breast Cancer Cells

Abstract: The noncoding RNA miR-125b has been described to reduce ErbB2 protein expression as well as proliferation and migration of cancer cell lines. As additional target of miR-125b, we identified the c-raf-1 mRNA by sequence analysis. We designed a short hairpin-looped oligodeoxynucleotide (ODN) targeted to the same 3′ untranslated region of c-raf-1 mRNA as miR-125b. The fully complementary ODN antisense strand is linked to a second strand constituting a partially double-stranded structure of the ODN. Transfection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 64 publications
1
25
0
3
Order By: Relevance
“…Raf-1 has been found to be overexpressed or overactivated in a variety of cancers, including renal cell carcinoma, hepatocellular carcinoma, non-small cell lung cancer, melanoma, and papillary thyroid carcinoma (32). Recently, Raf-1 was found to be a target of miR-7 and miR-125b (33,34). In breast cancer, miR-125b could target the same region of c-Raf-1 (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raf-1 has been found to be overexpressed or overactivated in a variety of cancers, including renal cell carcinoma, hepatocellular carcinoma, non-small cell lung cancer, melanoma, and papillary thyroid carcinoma (32). Recently, Raf-1 was found to be a target of miR-7 and miR-125b (33,34). In breast cancer, miR-125b could target the same region of c-Raf-1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Raf-1 was found to be a target of miR-7 and miR-125b (33,34). In breast cancer, miR-125b could target the same region of c-Raf-1 (34). In addition, Raf-1 was identified as a direct target of miR-7 in several cancer cell lines, including breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-125b promotes the proliferation of glial cells 7 but suppresses the proliferation of ovarian, bladder, breast and liver cancer cells. 6,[11][12][13] Regulators of proliferation, including BCL3, CDKN2A, E2F3, RAF1, ETS1, LIN28B2, ERBB3, ERBB2 and placenta growth factor 6,7,[11][12][13][14][15][16] have been identified as direct targets of miR-125b. It has been shown that overexpression of miR-125b inhibits apoptosis in glioma and prostate cancer cells, and miR-125b regulates the expression of pro-apoptotic proteins such as p53, Bak1, Puma and Bmf.…”
Section: Introductionmentioning
confidence: 99%
“…Another confirmed target of miR-125 family is MUC I (Mucin I) oncogene in breast cancer (Rajabi et al, 2010). In addition, a short hairpin DNA analogous to miR-125b was used to target C-Raf expression and this negatively affected the proliferation and survival of breast cancer cells (Hofmann et al, 2009). miR-125b was also reported to have negative effects on cellular proliferation of breast cancer cells in an ERBB2 dependent manner (Scott et al, 2007).…”
mentioning
confidence: 99%